2015
DOI: 10.1038/srep17802
|View full text |Cite
|
Sign up to set email alerts
|

A composite scaffold of MSC affinity peptide-modified demineralized bone matrix particles and chitosan hydrogel for cartilage regeneration

Abstract: Articular cartilage injury is still a significant challenge because of the poor intrinsic healing potential of cartilage. Stem cell-based tissue engineering is a promising technique for cartilage repair. As cartilage defects are usually irregular in clinical settings, scaffolds with moldability that can fill any shape of cartilage defects and closely integrate with the host cartilage are desirable. In this study, we constructed a composite scaffold combining mesenchymal stem cells (MSCs) E7 affinity peptide-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 45 publications
0
69
0
Order By: Relevance
“…DBM also contains a large amount of BMP and has shown osteoinductive potential in vivo [29]. BMSCs are a promising seed-cell source for bone repair, which can be achieved using micro-fracture surgery [30]. Thus, combining BMSCs with DBM should have a synergistic effect on the treatment of bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…DBM also contains a large amount of BMP and has shown osteoinductive potential in vivo [29]. BMSCs are a promising seed-cell source for bone repair, which can be achieved using micro-fracture surgery [30]. Thus, combining BMSCs with DBM should have a synergistic effect on the treatment of bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels with highly hydrated polymer networks mimic the native ECM while porous scaffolds provide for superior mechanical properties and mass transport of nutrients and wastes. Many studies have indicated that MSC‐laden hydrogels improved cartilage repair . However, those cell‐laden constructs were lack of mechanical strength.…”
Section: Applications Of Substrate‐derived Spheroids In Tissue Regenementioning
confidence: 99%
“…Moreover, 19.7% of the studies evaluated CS in the regeneration of skin [24, 27, 29, 6371], 14.7% in nervous tissue [30, 72–79], 11.5% in cartilage [32, 8184, 87, 88], and 3.3% in periodontal [33, 90] structures. The remaining studies involved regeneration of colorectal [26], mammary [89], tympanic membrane [31], and vascular [34] tissues (1.6% each).…”
Section: Resultsmentioning
confidence: 99%